THE EFFECT OF PRODUCT QUALITY AND SALES PROMOTION ON CONSUMER PURCHASE DECISIONS WITH SATISFACTION AS A MEDIATION VARIABLE IN ALAS COFFEE, TEMBARAK DISTRICT, TEMANGGUNG REGENCY - Chrisdinata Adi Mahendra; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (IAIN Surakarta, 2022)
The research entitled The Effect of Goods Quality and Sales Promotion on Purchase Decisions with Satisfaction as a Mediation Variable in Alas Coffee, Tembarak District, Temanggung Regency, aims to determine the effect of goods quality on consumer purchasing decisions, determine the effect of sales promotion on purchasing decisions, determine the effect of product quality and sales promotion together on consumer purchasing decisions at Alas Coffee Temanggung and determine the effect of product quality and promotion on purchasing decisions with satisfaction as a mediation. The research method used descriptive and quantitative methods. The population in this study were consumers who use coffee sales services at Alas Coffee Temanggung. The survey results while Alas Coffee consumers reached 200 people. The number was 50% of the population, so the number of samples was 100 respondents. The results show that product quality has a significant effect on purchasing decisions, promotion has a significant effect on purchasing decisions, product quality and promotion together has a significant effect on purchasing decisions at Alas coffee. Product quality has a significant effect on purchasing decisions at pedestal coffee with satisfaction as a mediation and promotion has a significant effect on purchasing decisions at Alas coffee with satisfaction as a mediation.